Challenges in the management of chronic wound infections. (September 2021) - Falcone, Marco; De Angelis, Barbara; Pea, Federico; Scalise, Alessandro; Stefani, Stefania; Tasinato, Rolando; Zanetti, Orazio; Dalla Paola, Luca
Highlights: Distinction between chronic uninfected from infected wounds is challenging. Culturing of all chronic wounds is inappropriate. Debridement is an important step to facilitate the wound healing process. Patients with chronic wound infections require a multidisciplinary approach. Systemic antibiotics should not be limited to infected cases. ABSTRACT: Objectives: Chronic wound infections may delay the healing process and are responsible for a significant burden on healthcare systems. Since inappropriate management may commonly occur in the care of these patients, this review aims to provide a practical guide underlining actions to avoid in the management of chronic wound infections. Methods: We performed a systematic review of the literature available in PubMed in the last 10 years, identifying studies regarding the management of patients with chronic wound infections. A panel of experts discussed the potential malpractices in this area. A list of 'Don'ts', including the main actions to be avoided, was drawn up using the 'Choosing Wisely' methodology. Results: In this review, we proposed a list of actions to avoid for optimal management of patients with chronic wound infections. Adequate wound bed preparation and wound antisepsis should be combined, as the absence of one of them leads to delayed healing and a higher risk of wound complications. Moreover, avoiding inappropriate use of systemic antibiotics is an important point because of the risk of selection of multidrug-resistant organisms as well as antibiotic-related adverse events. Conclusion: A multidisciplinary team of experts in different fields (surgeon, infectious disease expert, microbiologist, pharmacologist, geriatrician) is required for the optimal management of chronic wound infections. Implementation of this approach may be useful to improve the management of patients with chronic wound infections.